2018
DOI: 10.3892/ol.2018.8454
|View full text |Cite
|
Sign up to set email alerts
|

Dioscin suppresses the viability of ovarian cancer cells by regulating the VEGFR2 and PI3K/AKT/MAPK signaling pathways

Abstract: Diosgenin is a natural steroidal saponin that is extracted from a range of sources, including from fenugreek. It is a critical raw material in the synthesis of steroid hormone drugs, exhibiting antitumor, anti-inflammatory, antioxidation and a number of other significant pharmacological actions, possessing high pharmaceutical value. The aim of the present study was to investigate the effects of dioscin suppression on ovarian cancer cell growth and the mechanism of apoptosis induction by dioscin in ovarian canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Dioscin treatment increased cellular apoptosis in ovarian cancer SK-OV-3 cells in a dose-dependent manner. At the concentrations of 2.5 or 5 lM it significantly decreased PI3K and phosphorylated (p)-AKT, VEGFR2 protein expression compared with the non-treated control group, and induced expression of p-p38 protein (Guo and Ding 2018). Dioscin induced apoptosis in SGC-7901 cells in a dose-dependent manner (Hu et al 2011).…”
Section: Results Of In Vivo Studiesmentioning
confidence: 99%
“…Dioscin treatment increased cellular apoptosis in ovarian cancer SK-OV-3 cells in a dose-dependent manner. At the concentrations of 2.5 or 5 lM it significantly decreased PI3K and phosphorylated (p)-AKT, VEGFR2 protein expression compared with the non-treated control group, and induced expression of p-p38 protein (Guo and Ding 2018). Dioscin induced apoptosis in SGC-7901 cells in a dose-dependent manner (Hu et al 2011).…”
Section: Results Of In Vivo Studiesmentioning
confidence: 99%
“…Dioscin could suppress the VEGF-induced blood vessel formation and downregulate VEGFR2 and its downstream protein kinases phosphoinositide 3-kinase (PI3K), Src, FAK, AKT, phosphorylated p38 mitogen-activated protein kinase (MAPK), and Erk1/2 expression. Phosphorylated P38 MAPK was upregulated in the human umbilical vein endothelial cells (HUVECs) [65] but decreased in ovarian cancer SKOV3 cells [66], the difference may be related to the different cell types. The in vivo studies also confirmed that dioscin could attenuate invasion and migration, decrease tumor size, and extend the lifespan of rats [53, 54].…”
Section: Antitumormentioning
confidence: 99%
“…Interestingly, 4 showed the most potent anticancer effect, and the other compounds were less effective than 4 . Dioscin ( 4 ) has already been shown to inhibit the growth of colon, ovarian, and lung cancer and to be effective in apoptosis of cancer cells [41,42,43]. The anticancer effect caused by 4 examines whether the anticancer effect of osteosarcoma also uses the mitochondria signal pathway.…”
Section: Resultsmentioning
confidence: 99%